Relationship between Level of Knowledge and 5 moment Hand Hygiene Practice among Assistant Healthcare in Malaysia Teaching Hospital. - Wan Ahmad, Wan Latifah; Musa, Mazlinda; Hassan, Hamidah; Mamat, Rohani; Dewi, Enita; Abd Kassim, Sharina; Sa'at, Siti Fatimah; Baddiri, Baidi (Universitas Muhammadiyah Surakarta, 2024)
Hand hygiene is a handwashing method that significantly lowers the likelihood of pathogens (dangerous germs) on the hands. While assistant healthcare workers are part of the healthcare team, they always deal with patients' care but did not get proper training like nurses or doctors before becoming assistant healthcare This study is to assess the relationship between level of knowledge and five moments hand hygiene practice among assistants healthcare in one of the teaching hospitals in Malaysia. A cross-sectional research methodology was used; 154 Assistants healthcarewere chosen using random number generators after the sample size was calculated. The Knowledge, Attitude, and Practice on Hand Hygiene questionnaire used was adopted from WHO publications. The ANOVA revealed a significant effect of Level of Knowledge on Level of Practice (F(1, 152) = 3.416, p = 0.006). Specifically, for each unit increase in Level of Knowledge, Level of Practice increased by 57.725 units (β = 57.725, p = 0.006). These findings emphasise the need for targeted interventions and training programmes aimed at bridging the knowledge-practice divide and eventually raising hand hygiene compliance in the medical setting